Students' Response to The Development of U-GEO Media Trading Card Game (TCG) with Teams Games Tournament (TGT) - Fahmi Imamul Habiby; Rindawati Rindawati; Bambang Sigit Widodo (Jurnal Pendidikan : Riset dan Konseptual, 2023)
The results of observations in class XI Social Sciences, the learning media used were only blackboards and PowerPoint. The media can make students bored and unable to attract interest in learning. This study aims to determine students' responses to TGC learning media on the material of cultural diversity in Bangkalan. Research using descriptive method with a quantitative approach. Data collection tool used is a questionnaire sheet. The data analysis technique used in this study is data reduction, data presentation and conclusion. The results showed that the percentage of responses of students in class XI IPS SMAN 1 Bangkalan to TGC learning media on the cognitive dimension indicators of content understanding averaged 86.2%, indicators of clarity of learning instructions and information averaged 86% and indicators of suitability of the average card display average 87.8%. On the affective dimension of student responses on motivation indicators obtained an average percentage of 86.8%, attractiveness indicators an average of 89.8% and curiosity indicators an average of 85.6%. On the conative dimension, the response of students to the indicator asking an average of 86.6% and the indicator responding to questions is an average of 95.6%.